1990
DOI: 10.1161/01.str.21.11.1607
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of a monosialoganglioside derivative following transitory forebrain ischemia in rats.

Abstract: We evaluated the effects of treatment with the inner ester derivative of the monosialoganglioside GM1 on cortical electroencephalographic activity and hippocampal CA1 morphology after transitory, near-complete cerebral ischemia in rats. Ischemia was induced by the four-vessel occlusion method, and we studied only the 58 rats that showed amino acid neurotransmission plays an important role. Neurons selectively vulnerable to an ischemic episode receive prominent excitatory amino acid transmitter inputs, and abla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

1992
1992
2008
2008

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…1B) and LPS-and IFN-γ-treated microglia (data not shown). Furthermore, several studies indicated that gangliosides increase the rates of neuritogenesis both in vivo and in vitro (Ferrari et al, 1983;Mendez-Otero and Santiago, 2003;Roisen et al, 1984) and possess a neuroprotective action (Favaron et al, 1988;Geisler et al, 1991;Karpiak et al, 1990;Manev et al, 1990;Seren et al, 1990). These effects have partly been explained by the fact that GM1 induces a rapid and significant increase in the amount of NT-3, which was observed in fibroblast cells and cerebellar granule cells (Rabin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…1B) and LPS-and IFN-γ-treated microglia (data not shown). Furthermore, several studies indicated that gangliosides increase the rates of neuritogenesis both in vivo and in vitro (Ferrari et al, 1983;Mendez-Otero and Santiago, 2003;Roisen et al, 1984) and possess a neuroprotective action (Favaron et al, 1988;Geisler et al, 1991;Karpiak et al, 1990;Manev et al, 1990;Seren et al, 1990). These effects have partly been explained by the fact that GM1 induces a rapid and significant increase in the amount of NT-3, which was observed in fibroblast cells and cerebellar granule cells (Rabin et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…A similar protection is elicited by parenteral GM1 (II3-N-acetylneuraminosylgangliotetraosylceramide) administration to rats, cats, and dogs when glutamate in brain interstitial fluids is enhanced by a hypoxia secondary to trauma or to various forms of impairment of cardiovascular function, including the experimental occlusion of the middle cerebral artery (MCA) (5)(6)(7)(8)(9)(10)(11)(12). In addition, GM1 administered parenterally to patients a few hours after spinal cord injury or stroke can improve functional recovery (13)(14)(15).…”
mentioning
confidence: 92%
“…The beneficial effects reported by various investigators in a number of animal models of Parkinson disease (Hadjiconstantinou et al, 1986;Schneider et al, 1992) and ischemic brain damage (Hoermann, 1988;Karpiak et al, 1990;Seren et al, 1990;Somjen et al, 1990;Bharucha et al, 1991;Costa et al, 1992;Kharlamov et al, 1993) following parenteral administration of GM1 prompted us to investigate whether an oral treatment with semisynthetic gangliosides such as LIGA20 could become a suitable therapeutic strategy to prevent neuronal damage owing to recurrent release of excitotoxins as it may occur in epilepsy (Olney, 1990;Chapman, 1992) or in minor thrombosis (McCulloch et al, 1991;Zivin and Choi, 1991) in elderly hypertensive patients that have already experienced a first episode of stroke, and in Parkinson disease (Klockgether and Turski, 1989), or in cardiosurgery during prolonged extracorporeal circulation or prolonged hypothermic circulatory arrest (Redmond et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…and semisynthetic [LIGA4 (113-Neu-5-AcGgOse 4-2D-erythro-1, 3-dihydroxy-2-acetylamide-4-transoctadecene), or LIGA20 (113-Neu-5-AcGgOse4-2D-erythro-1,3-dihydroxy-2-dichloroacetylamide-4-trans-octadecene) ] glycosphingolipids protected against glutamate-induced neuronal death when added to primary neuronal cultures (Manev et al, 1990a) or when given parenterally to rats successively exposed to brain hypoxic or anoxic conditions (Karpiak et al, 1990;Seren et al, 1990;Manev et al, 1990b;Bharucha et al, 1991;Costa et al, 1992;Kharlamov et al, 1993). Recently GM1 administered parenterally to dogs has been reported to reach the brain in concentrations that reduce the glutamate-mediated neurologic injury associated with hypothermic circulatory arrest (Redmond et al, 1993).…”
Section: Introductionmentioning
confidence: 99%